MULTIMEDIA STREAMING (AUDIO VIDEO) BY USING MULTICAST VIDEOLAN CLIENT (VLC) 0.7.2 VERSION OF WINDOWS OPERATING SYSTEM - Ridwan Ridwan; Fivtatianti H., Skom., MM (Jurnal Sistem Komputer, 2005)
At this writing discusses about Streaming Multimedia (Audio Video) by Multicast using Videolan Client (VLC) Player Version 0.7.2 on Windows Operating System. Multimedia streaming is done so that the needs of service for users of communication services can be met primarily Multimedia information (in this case the media Audio and Video). Multicast is a standardized method for sending a presentation to a large number of users over a network or the Internet. Multicast is the ability of the network (network) communication to receive data from a source and convey it spread to many destinations.